Unlocking Math Success: Effect of an Intervention Program on Fifth Graders - Leonano, Adora; Jhacell, De Rosas; Reyes, Jocelyn (JPAIR Multidisciplinary Research, 2024)
Mathematics education aims to enhance students' computational skills and problem-solving abilities, as outlined in the numeracy curriculum. However, addressing the diverse needs of learners, particularly in terms of numerical skills, remains a challenge for many schools and educators. The primary objective of this study was to evaluate the effectiveness of the Mathematics Intervention Program (MIP) designed to reduce low performance among fifth graders. The study employed a quasi-experimental research design with 93 participants from Calamba Elementary School, focusing on the significant portion of students—75.3%—who were identified as low achievers based on result of the second periodical test. Pre-tests and post-tests were utilized to collect data, which were analyzed using statistical tools such as frequency distribution, percentage, mean, Mean Percentage Score (MPS), standard deviation, and the t-test. Results indicated a significant improvement in students' mathematical performance after the intervention. The findings provide strong evidence that the MIP, which incorporates the Concrete Pictorial Abstract (CPA) approach and explicit instruction, is effective in enhancing mathematical proficiency and addressing foundational gaps in numeracy.
Keywords: Intervention Program in Mathematics; Innovative Learning Materials; Fourth Graders; Quasi-experimental Study; Calamba City; Philippines